Efficient aqueous zinc ion negative electrode plate and preparation method thereof

By coating carbon nitride and zinc titanate coatings on the surface of the zinc sheet, the interface side reaction and dendrite growth problems of the negative electrode of the aqueous zinc ion battery are solved, the cycle life and ion transmission performance of the battery are improved, and more efficient batteries are achieved stability.

CN119208775APending Publication Date: 2024-12-27CHANGZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411315995.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The zinc metal negative electrode of aqueous zinc ion batteries has a short cycle life and a slow transmission rate due to interfacial side reactions and dendrites growth, which limits its development.

Method used

The surface of the zinc sheet is coated with carbon nitride coating and zinc titanate coating in turn. The carbon nitride coating consists of graphite phase g-C3N4 and a binder. The zinc titanate coating is composed of zinc titanate powder and a binder. Composition, through this structure, dendrites' growth and side reactions are inhibited, and the transmission kinetics of zinc ions are improved.

Benefits of technology

It significantly improves the cycle life and ionic conductivity of zinc ion batteries, prevents side reactions and dendrites from growing, and enhances the stability and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208775A_ABST
    Figure CN119208775A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of aqueous zinc ion battery negative electrode materials, in particular to an efficient aqueous zinc ion negative electrode plate and a preparation method thereof. A zinc metal negative electrode of an aqueous zinc ion battery has many interface side reactions and is easy to grow dendrites, so that the cycle life of the battery is relatively short. In order to solve the problems, the invention provides the efficient aqueous zinc ion negative plate which is formed by sequentially coating the surface of a Zn plate with a carbon nitride coating and a zinc titanate coating, carbon nitride in the carbon nitride coating is graphite-phase carbon nitride, and the graphite-phase carbon nitride is stable in property, large in specific surface area and rich in sp2 hybridized nitrogen atoms, so that the specific surface area of the graphite-phase carbon nitride is increased, and the specific surface area of the graphite-phase carbon nitride is increased. The nitrogen source has relatively high electronegativity and zinc affinity, generates an adsorption effect on zinc ions, forms a Zn-N bond, can promote nucleation of the zinc ions and reduce a nucleation barrier of Zn < 2 + > ions, and the carbon nitride coating is loose and porous in structure, is not stable enough in structure and is easy to fall off from the surface of an electrode in the charge-discharge cycle process of the battery, so that the performance of the battery is improved. According to the invention, the zinc titanate coating is arranged on the surface of the carbon nitride coating, and the zinc titanate coating with a compact structure can effectively prevent the carbon nitride coating from being in direct contact with an electrolyte, so that the cycling stability of the battery is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aqueous zinc ions, and in particular to a high-efficiency aqueous zinc ion negative electrode sheet and a preparation method thereof. Background Art

[0002] Aqueous zinc-ion batteries are one of the most promising post-lithium-ion battery technologies, suitable for large-scale energy storage due to their affordable, safe, and environmentally friendly advantages. More importantly, zinc metal as the negative electrode has a low redox potential (-0.76 V compared to standard hydrogen electrode) and a high theoretical capacity (820 mAh g -1 ). However, Zn metal anodes are plagued by interfacial side reactions and dendrite growth, resulting in poor reversibility, low Coulombic efficiency and reduced cycle life.

[0003] To address these issues, great efforts have been made to regulate the environment of the Zn anode / electrolyte interface, including designing the Zn anode structure, developing advanced separators, and constructing interfacial protective layers. The construction of an interfacial protective layer is considered to be one of the most direct and attractive methods due to its simple and easy-to-adjust preparation characteristics. Some metal and carbon-based layers (such as In, carbon black, and activated carbon) can effectively redistribute the interfacial electric field and guide uniform deposition; non-conductive materials, such as CaCO3, TiO2, etc., can achieve 3D diffusion and promote uniform deposition. However, due to the poor zinc affinity and poor conductivity of zinc ions, the Zn 2+ The slow transport rate still limits their further development. Therefore, an artificial solid electrolyte interface (SEI) layer with high ionic conductivity and low electrical conductivity properties is introduced.

[0004] Carbon nitride (C3N4) has five different types of structures (graphite-like structure phase, cubic phase, quasi-cubic phase, α phase and β phase structure). Studies have found that graphite phase carbon nitride (g-C3N4) has the most stable performance. In the graphite phase g-C3N4, when the six negatively charged N atoms locally form a strong annular negative micro-electric field, it is more conducive to capturing the positively charged Zn during the electroplating process. 2+ The micro-electric field plays a beneficial role in balancing the local electric field generated on the surface of zinc metal during the battery charging and discharging process, reducing the local electric field-induced Zn 2+ Although Zn 2+ Nucleation continues, but the graphite phase g-C3N4 interface layer has achieved the effect of inhibiting dendrites.

[0005] However, the graphite phase g-C3N4 interface layer still has certain disadvantages as a SEI membrane. For example, its loose and porous nature cannot effectively inhibit the side reactions occurring at the zinc negative electrode interface. Summary of the invention

[0006] The problem in the prior art is that the zinc metal negative electrode of the aqueous zinc ion battery has many interface side reactions and is prone to dendrite growth, resulting in a short battery cycle life. In view of the above problems, the present invention provides a high-efficiency aqueous zinc ion negative electrode sheet, which is formed by coating a carbon nitride coating and a zinc titanate coating on the surface of the Zn sheet in sequence. When in use, the zinc titanate coating contacts the electrolyte.

[0007] The carbon nitride coating comprises a graphite phase g-C3N4 and a binder,

[0008] The zinc titanate coating comprises zinc titanate powder and a binder.

[0009] Preferably, the mass ratio of the graphite phase g-C3N4 to the binder in the carbon nitride coating is 7:3.

[0010] Preferably, the mass ratio of zinc titanate powder to binder in the zinc titanate coating is 9:1.

[0011] Preferably, the binder includes one or a combination of two or more of PVDF, PTFE, PVA, and modified SBR.

[0012] Preferably, the carbon nitride coating has a thickness of 10 μm.

[0013] Preferably, the zinc titanate coating has a thickness of 10 μm.

[0014] A high-efficiency aqueous zinc ion battery, the negative electrode material of which adopts the negative electrode sheet described above.

[0015] Preferably, the positive electrode active materials of the high-efficiency aqueous zinc ion battery include V2O5, VO2, NH4V4O 10 Or a mixture of CNT and MnO2.

[0016] Preferably, the electrolyte of the high-efficiency aqueous zinc ion battery is a mixed solution formed by a soluble zinc salt and deionized water.

[0017] Preferably, the soluble zinc salt includes one or a mixture of two or more of zinc sulfate, zinc chloride, zinc nitrate, zinc acetate, zinc trifluoromethanesulfonate, zinc perchlorate, zinc trifluoromethanesulfonyl imide, and zinc tetrafluoroborate.

[0018] The present invention has the following beneficial effects:

[0019] (1) The aqueous zinc ion battery negative electrode sheet obtained by the present invention is formed by coating a carbon nitride coating and a zinc titanate coating in sequence on the surface of a Zn sheet, wherein the carbon nitride in the carbon nitride coating is graphite phase carbon nitride.

[0020] Graphite carbon nitrides are stable, have large specific surface area and rich sp2 Hybridized nitrogen atoms, which have high electronegativity and zinc affinity, adsorb zinc ions to form Zn-N bonds, which can promote zinc ion nucleation and reduce Zn 2+ The present invention uses chitosan and melamine as raw material precursors of g-C3N4. Chitosan provides a small amount of carbon source, which makes the obtained g-C3N4 have a more regular molecular structure and good mechanical properties. The bridging N atoms in melamine are replaced by C atoms to form a delocalized large π bond, which is very beneficial to improving the ionic conductivity of the negative electrode sheet.

[0021] The outermost zinc titanate coating can not only prevent zinc metal from directly contacting the electrolyte, effectively preventing the occurrence of side reactions such as hydrogen evolution, but also zinc titanate can use its own rigidity to effectively solve the problem of side reactions on the zinc sheet surface caused by the loose and porous nature of the carbon nitride coating, thereby reducing the battery cycle life.

[0022] (2) The present invention has found that when melamine and chitosan are used as raw material precursors, the properties of carbon nitride obtained at different calcination temperatures are different. When they are used as active components in carbon nitride coatings, the cycle performance of the obtained negative electrode sheets is quite different. The results show that when the calcination temperature is 550°C, the performance of the obtained carbon nitride coating is the best, and thus the cycle performance of the obtained negative electrode sheet is also the best.

[0023] (3) The carbon nitride coating has a loose and porous structure. During the battery charge and discharge cycle, the structure is not stable enough and is easy to fall off from the electrode surface. The present invention provides a zinc titanate coating on the surface of the carbon nitride coating. The densely structured zinc titanate coating can effectively prevent the carbon nitride coating from directly contacting the electrolyte. Zinc titanate also has excellent zinc affinity and can absorb Zn in the electrolyte. 2+ , thereby improving the uniform Zn 2+ flux, significantly enhancing Zn 2+ The transmission kinetics performance of the battery is improved. In summary, the present invention uses such an internal zinc-philic and external hydrophobic negative electrode sheet to synergistically inhibit the growth of negative electrode dendrites and the occurrence of side reactions, thereby better improving the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 :The symmetrical battery obtained in Example 1 of the present invention is at 5 mA·cm -2 、1mAh·cm -2 XRD pattern of the negative electrode surface after 50 cycles under the same conditions. Bare Zn in the figure refers to bare zinc.

[0025] Figure 2 : The symmetrical battery obtained in Example 1 of the present invention at 1 mA·cm -2 、1mAh·cm -2The cyclic stability effect test diagram under different conditions. The Bare Zn in the figure refers to bare zinc.

[0026] Figure 3 : is a rate performance effect test diagram of the symmetrical battery obtained in Example 1 of the present invention, and the Bare Zn in the figure refers to bare zinc. DETAILED DESCRIPTION

[0027] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.

[0028] The Zn sheets used in the following examples of the present invention were prepared according to the following method:

[0029] A zinc foil with a thickness of 200 μm and a purity of 99.99% was polished once with 2000-mesh sandpaper, then ultrasonically cleaned with anhydrous ethanol for 10 minutes, and then dried in a vacuum oven at 60° C. for 600 minutes to obtain a clean zinc sheet.

[0030] The graphite phase g-C3N4 in the following embodiments of the present invention is prepared according to the following steps:

[0031] 3.0 g of melamine and 0.015 g of chitosan were thoroughly mixed, then placed in a 50 mL alumina crucible with a lid and placed in a muffle furnace, and heated in the muffle furnace from room temperature to 550 ° C and maintained at a constant temperature for 4 h. After cooling to room temperature, the obtained yellow block was crushed into powder and collected.

[0032] The zinc titanate powder in the following embodiments of the present invention is prepared according to the following steps:

[0033] Under vigorous stirring, 160 mL of ethylene glycol, 2.19 g of Zn(CH3COO)2 and 3.4 g of C 16 H 36 O4Ti were mixed evenly, and then 2.0g PVP was added to the mixed solution and stirred vigorously for 24h. Then the mixed solution was placed in a reactor and heated at 60°C for 24h. After the reaction, the reaction solution was centrifuged and washed with deionized water. The solid product was vacuum dried at 80°C for 12h and then calcined in air at 600°C for 6h.

[0034] Example 1

[0035] A high-efficiency aqueous zinc ion negative electrode sheet, which is formed by coating a carbon nitride coating and a zinc titanate coating on the surface of a Zn sheet in sequence.

[0036] The carbon nitride coating is formed by uniformly coating a coating formed by mixing graphite phase g-C3N4 with PVDF and NMP on the surface of the Zn sheet and vacuum drying at 60°C. The mass ratio of graphite phase g-C3N4 to PVDF in the coating is 7:3, and the solid content of the coating is 40%. The zinc titanate coating is formed by uniformly coating a coating formed by mixing zinc titanate powder with PVDF and NMP on the surface of the carbon nitride coating and vacuum drying at 60°C. In the coating, the mass ratio of zinc titanate powder to PVDF is 9:1, and the solid content of the coating is 50%.

[0037] The thickness of the carbon nitride coating is 10 μm, and the thickness of the zinc titanate coating is 10 μm.

[0038] Example 2 is the same as Example 1, except that PTFE is used in Example 2 to replace PVDF in Example 1.

[0039] Example 3 is the same as Example 1, except that PVA is used in Example 3 to replace the PVDF in Example 1.

[0040] Comparative Example 1 is the same as Example 1, except that the thickness of the carbon nitride coating in Comparative Example 1 is 15 μm.

[0041] Comparative Example 2 is the same as Example 1, except that the thickness of the carbon nitride coating in Comparative Example 2 is 5 μm.

[0042] Comparative Example 3 is the same as Example 1, except that the mass ratio of the graphite phase g-C3N4 to PVDF in the carbon nitride coating of Comparative Example 3 is 4:1.

[0043] Comparative Example 4 is the same as Example 1, except that the mass ratio of the graphite phase g-C3N4 to PVDF in the carbon nitride coating of Comparative Example 4 is 2:1.

[0044] Comparative Example 5 is the same as Example 1, except that the mass ratio of zinc titanate powder to PVDF in the zinc titanate coating of Comparative Example 5 is 7:3.

[0045] Comparative Example 6 is the same as Example 1, except that the thickness of the zinc titanate coating in Comparative Example 6 is 15 μm.

[0046] Comparative Example 7 is the same as Example 1, except that the thickness of the zinc titanate coating in Comparative Example 7 is 5 μm.

[0047] Comparative Example 8 is the same as Example 1, except that the graphite phase g-C3N4 in Comparative Example 8 is prepared according to the following steps:

[0048] 3.0 g of melamine and 0.015 g of chitosan were thoroughly mixed, then placed in a 50 mL alumina crucible with a lid and placed in a muffle furnace, and heated in the muffle furnace from room temperature to 500 ° C and maintained at a constant temperature for 4 h. After cooling to room temperature, the obtained yellow block was crushed into powder and collected.

[0049] Comparative Example 9 is the same as Example 1, except that the graphite phase g-C3N4 in Comparative Example 9 is prepared according to the following steps:

[0050] 3.0 g of melamine and 0.015 g of chitosan were thoroughly mixed, then placed in a 50 mL alumina crucible with a lid and placed in a muffle furnace, and heated in the muffle furnace from room temperature to 600 ° C and maintained at a constant temperature for 4 h. After cooling to room temperature, the obtained yellow block was crushed into powder and collected.

[0051] Comparative Example 10 is the same as Example 1, except that the negative electrode sheet in Comparative Example 10 is formed by coating a zinc titanate coating and a carbon nitride coating in sequence on the surface of a Zn sheet, and the carbon nitride coating is in direct contact with the electrolyte.

[0052] Comparative Example 11 is the same as Example 1, except that the surface of the negative electrode sheet in Comparative Example 11 is only provided with a carbon nitride coating, and no zinc titanate coating is provided.

[0053] Performance Testing

[0054] The negative electrode sheets obtained in Examples 1-3 and Comparative Examples 1-11 were cut into small discs with a diameter of 16 mm, and assembled into symmetrical batteries using CR-2016 battery shells; the structure and installation order inside the symmetrical battery are negative electrode shell, aqueous zinc ion battery negative electrode disc, two diaphragms (diameter 19 mm), aqueous zinc ion battery negative electrode disc, stainless steel gasket (diameter 14.5 mm, thickness 0.5 mm), stainless steel shrapnel, positive electrode shell. The battery packaging pressure is 50 GPa. The diaphragm uses glass fiber (GF / A) produced by Whatman. The electrolyte used is 3 mol / L trifluoromethanesulfonate zinc aqueous solution, and the electrolyte usage of a single battery is 100 μL, and the electrolyte is added after a diaphragm is placed.

[0055] Cycle life tests were performed on the symmetrical batteries obtained in Examples 1-3 and Comparative Examples 1-10, respectively, and the test conditions were as follows:

[0056] The symmetrical battery cycle stability test was carried out at room temperature, and the battery test equipment used was the Shenzhen Xinwei test system. The test program settings were static, constant current discharge, constant current charge, cycle and end. The static time was 2 hours, and the constant current discharge and constant current charge times were set to 60 minutes respectively. One cycle includes one constant current discharge and one constant current charge, which are counted through the cycle program. The test can be stopped at any time during the test to obtain the symmetrical battery cycle time (the cycle time is 120 minutes). The current density of each battery negative electrode disc is set to 1.0mA / cm 2 , the cycle life of the symmetrical battery is shown in Table 1.

[0057] The specific test results are shown in Table 1:

[0058] Table 1

[0059] Test items Cycle life (h) Example 1 1002 Example 2 762 Example 3 757 Comparative Example 1 833 Comparative Example 2 821 Comparative Example 3 816 Comparative Example 4 724 Comparative Example 5 737 Comparative Example 6 805 Comparative Example 7 811 Comparative Example 8 798 Comparative Example 9 744 Comparative Example 10 719 Comparative Example 11 405

[0060] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A high-efficiency aqueous zinc ion negative electrode sheet, characterized in that: It is formed by coating a carbon nitride coating and a zinc titanate coating on the surface of a Zn sheet in sequence. When in use, the zinc titanate coating contacts the electrolyte. The carbon nitride coating comprises a graphite phase g-C3N4 and a binder, The zinc titanate coating comprises zinc titanate powder and a binder.

2. A high-efficiency aqueous zinc ion negative electrode sheet according to claim 1, characterized in that: The mass ratio of the graphite phase g-C3N4 to the binder in the carbon nitride coating is 7:

3.

3. A high-efficiency aqueous zinc ion negative electrode sheet according to claim 1, characterized in that: The mass ratio of zinc titanate powder to binder in the zinc titanate coating is 9:

1.

4. A high-efficiency aqueous zinc ion negative electrode sheet according to claim 1, characterized in that: The binder includes one or a combination of two or more of PVDF, PTFE, PVA and modified SBR.

5. The high-efficiency aqueous zinc ion negative electrode sheet according to claim 1, characterized in that: The thickness of the carbon nitride coating is 10 μm.

6. A high-efficiency aqueous zinc ion negative electrode sheet according to claim 1, characterized in that: The thickness of the zinc titanate coating is 10 μm.

7. A high-efficiency aqueous zinc ion battery, characterized in that: The negative electrode material is the negative electrode sheet described in any one of claims 1 to 6.

8. A high-efficiency aqueous zinc ion battery according to claim 7, characterized in that: Positive electrode active materials include V2O5, VO2, NH4V4O 10 Or a mixture of CNT and MnO2.

9. A high-efficiency aqueous zinc ion battery according to claim 7, characterized in that: The electrolyte is a mixed solution formed by soluble zinc salt and deionized water.

10. A high-efficiency aqueous zinc ion battery according to claim 9, characterized in that: The soluble zinc salt includes one or a mixture of two or more of zinc sulfate, zinc chloride, zinc nitrate, zinc acetate, zinc trifluoromethanesulfonate, zinc perchlorate, zinc trifluoromethanesulfonyl imide, and zinc tetrafluoroborate.

Citation Information

Cited By

  • Preparation process of heterogeneous metal interface material for aqueous zinc battery

    CN120666323A